Different Visual Weighting due to Fast or Slow Vestibular Deafferentation: Before and after Schwannoma Surgery - Fredrik Tjernström; Per-Anders Fransson; Babar Kahlon; Mikael Karlberg; Sven Lindberg; Peter Siesjö; Måns Magnusson (Neural Plasticity)
Background. Feedback postural control depends upon information from somatosensation, vision, and the vestibular system that are weighted depending on their relative importance within the central nervous system. Following loss of any sensory component, the weighting changes, e.g., when suffering a vestibular loss, the most common notion is that patients become more dependent on visual cues for maintaining postural control. Dizziness and disequilibrium are common after surgery in schwannoma patients, which could be due to interpretation of the remaining sensory systems involved in feedback-dependent postural control and spatial orientation. Objective. To compare visual dependency in spatial orientation and postural control in patients suffering from unilateral vestibular loss within different time frames. Methods. Patients scheduled for schwannoma surgery: group 1 (n=27) with no vestibular function prior to surgery (lost through years), group 2 (n=12) with remaining vestibular function at the time of surgery (fast deafferentation), and group 3 (n=18) with remaining function that was lost through gentamicin installations in the middle ear (slow deafferentation). All patients performed vibratory posturography and rod and frame investigation before surgery and 6 months after surgery. Results. Postural control improved after surgery in patients that suffered a slow deafferentation (groups 1 and 3) (p<0.001). Patients that suffered fast loss of remaining vestibular function (group 2) became less visual field dependent after surgery (p≤0.035) and were less able to maintain stability compared with group 1 (p=0.010) and group 3 (p=0.010). Conclusions. The nature and time course of vestibular deafferentation influence the weighting of remaining sensory systems in order to maintain postural control and spatial orientation.